Household Welfare Impacts of China's Accession to the World Trade Organization - Ravallion, Martin, 1952- 1952- (The World Bank, 2003)
Chen and Ravallion use China's national household surveys for rural and urban areas to measure and explain the welfare impacts of the changes in goods and factor prices attributed to WTO accession. Price changes are estimated separately using a general equilibrium model to capture both direct and indirect effects of the initial tariff changes. The welfare impacts are first-order approximations based on a household model incorporating own-production activities and are calibrated to the household-level data imposing minimum aggregation. The authors find negligible impacts on inequality and poverty in the aggregate. However, diverse impacts emerge across household types and regions associated with heterogeneity in consumption behavior and income sources, with possible implications for compensatory policy responses. This paper—a product of the Poverty Team, Development Research Group—is part of a larger effort in the group to assess the household welfare impacts of economywide policy changes